2016
DOI: 10.1016/j.bmc.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the first small-molecule inhibitor of the REV7 DNA repair protein interaction

Abstract: DNA interstrand crosslink (ICL) repair (ICLR) has been implicated in the resistance of cancer cells to ICL-inducing chemotherapeutic agents. Despite the clinical significance of ICL-inducing chemotherapy, few studies have focused on developing small-molecule inhibitors for ICLR. The mammalian DNA polymerase ζ, which comprises the catalytic subunit REV3L and the non-catalytic subunit REV7, is essential for ICLR. To identify small-molecule compounds that are mechanistically capable of inhibiting ICLR by targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…2), an inhibitor of the interaction of REV7 with the REV7-binding sequence of REV3L. 19 In the thermal shi assay, compound 1 showed a clear shi in the denaturation point of the His-REV7(R124A)/REV3L(1847-1898) complex, suggesting that compound 1 exchanged with REV3L(1847-1898) in the complex but was not nonspecically bound on the complex. The pull-down assay also indicated that both compound 1 and REV3L(1875-1895) can exchange with the biotin-AviTa-gREV3L(1846-1898) in the complex, resulting in the release of His-REV7(R124A) from the beads.…”
Section: Introductionmentioning
confidence: 99%
“…2), an inhibitor of the interaction of REV7 with the REV7-binding sequence of REV3L. 19 In the thermal shi assay, compound 1 showed a clear shi in the denaturation point of the His-REV7(R124A)/REV3L(1847-1898) complex, suggesting that compound 1 exchanged with REV3L(1847-1898) in the complex but was not nonspecically bound on the complex. The pull-down assay also indicated that both compound 1 and REV3L(1875-1895) can exchange with the biotin-AviTa-gREV3L(1846-1898) in the complex, resulting in the release of His-REV7(R124A) from the beads.…”
Section: Introductionmentioning
confidence: 99%
“…DNA binding REV7 specific compounds [175][176][177][178][179][180] FANCW/RFWD3 6CVZ E3 FANCQ/XPF 1Z00, 2A1J, 2AQ0, 2KN7, 2MUT DNA incision [181][182][183][184][185]…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Moreover, while several small molecule inhibitors of TLS components have been discovered, none of them were shown to have activity in vivo (204). Examples comprise previously described selective inhibitors of REV7 (205), oxetanocin derivatives inhibiting Pol η (206), or small molecule compounds blocking the interaction between components of the Pol ζ complex (207). One example of a small inhibitor shown to be active in vivo is a recently described molecule JH-RE-06.…”
Section: Alterations Of Ddt Pathways In Cancermentioning
confidence: 99%